Intervention for Symptom Cluster Management of Fatigue, Loss of Appetite, and Anxiety among Patients with Lung Cancer undergoing Chemotherapy - Thidarat Khamboon; Intira Pakanta (Elsevier, 2021)
Objective: Patients with lung cancer can experience various distressing symptoms. The present study aims to use symptom cluster management intervention based on symptom management theory to moderate the severity of symptom clusters, including fatigue, loss of appetite, and anxiety, in patients with lung cancer undergoing chemotherapy. Methods: A quasi-experimental study was conducted using historical controls to assess and compare the effect of a novel symptom cluster management intervention on the severity of fatigue, loss of appetite, and anxiety in patients with lung cancer undergoing chemotherapy. Lung cancer patients were recruited from an outpatient chemotherapy unit at a university hospital in Thailand. Eighty participants were assigned equally to the experimental and control groups. The study outcomes, including fatigue, loss of appetite, and anxiety, were assessed with the Edmonton Symptom Assessment System at baseline and days 7, 14, and 28 postintervention. Repeated-measures ANOVA was analyzed to determine mean differences between groups across time. Results: Overall, anxiety decreased gradually on days 7, 14, and 28 (P < 0.001 for all time points) in the experimental group. Fatigue and loss of appetite also declined after days 14 (P < 0.001) and 28 (P < 0.001) compared to baseline. The significant effects of the interaction terms time × group (P < 0.001) for all symptoms within the cluster indicate the benefit of the intervention over time. Conclusions: The pattern of changes in the symptom cluster across the study period was significantly different between the two study groups. Patients in the experimental group reported an improvement in fatigue, loss of appetite, and anxiety over time after receiving the intervention. The results suggested that the symptom cluster management intervention provided a promising approach for the simultaneous treatment of multiple symptoms within a cluster.